Perlindungan Hukum Pemilik Hak Publisitas Potret dalam Novel Fanfiksi yang Dikomersialkan - witriani; Rembrandt Rembrandt; Yussy Adelina Mannas (Lareh Law Review, 2023)
The allure attached to famous figures brings economic value that should be considered and protected. When a commercially marketed fanfiction novel uses the portrait of a famous figure as its cover, questions arise about whether the used portrait has obtained permission. This is where the importance of the right to publicity for the inherent characteristics of famous figures comes into play, needing to be upheld as a property right because portraits are protected as economically oriented intellectual property. This article will discuss how the regulation, government role, and protection of portrait publicity rights in Indonesia are approached through a juridical empirical and descriptive-analytical perspective. The article concludes that portrait publicity rights are regulated in Article 9 and Article 12 paragraphs (1) and (2) of Copyright Law No. 28 of 2014. The state provides legal protection for owners of portrait publicity rights, both preventive and punitive protection. Preventive protection involves announcing the creation of the portrait, registering the portrait with the Directorate General of Intellectual Property, and creating a license agreement between the licensor and licensee to later be registered with the Ministry of Law and Human Rights, as portraits are considered intangible movable property, and their transfer is done in writing. On the other hand, punitive protection against commercially exploited portraits consists of non-litigation avenues (arbitration and alternative dispute resolution) and litigation avenues (courts). The government has a role in monitoring the creation and distribution of copyright infringement content.